Building teacher professional capabilities through transformative learning. Issue 4 (8th August 2021) - Nolan, Andrea; Molla, Tebeje
ABSTRACT: Promoting teacher professionalisation has become a key policy agenda in Australia and internationally. Professional learning is often invoked as a means to achieve this goal. In this paper, drawing on findings of a series of studies we conducted on the topic in the Early Childhood Education and Care sector, and guided by a range of theoretical tools, we propose a three-step cyclical approach to understanding, assessing and promoting teacher professional learning. The first step introduces spaces of assessment of teacher professional functioning. The second step outlines the core elements of transformative teacher professional learning. The third step highlights two interrelated aspects of teacher professional capabilities: confidence and agency. This work has been guided by the research question: How can teacher professionalisation be understood, assessed and advanced? In closing, we briefly state the implications of the findings for policy and practice.